#### Answer

x=(-1)

#### Work Step by Step

1) Write the equation; 4(x+5)=-3(x-2)+7
2) Distribute the "4" and "-3" on both sides
3) After distributing, you should gain; 4x+20=-3x+6+7
4) Combine like terms
5) The answer should be 4x+20=-3x+13
6) Now put the variable (which is "x") to one side, and the non-variable numbers to one side; simplify
7) After simplifying, you should obtain; 7x=-7
8) Divide the ENTIRE equation with the number with the variable (which is "+7")
9) You should get; x=-7/7
10) Simplify: x=-1